O índice de massa corporal e os desfechos da fertilização in vitro - Dornelles, Victória Campos (2021)
Introduction: Overweight is a risk factor for fertility mainly due to ovulation disorders; However, data about its impact on assisted reproduction techniques outcomes remain conflicting. Despite the well-established obesity risk factor for adverse perinatal outcomes in spontaneous pregnancies, there are still no studies evaluating this effect in pregnancies resulting from ART. Thus, the main objective of this study was to evaluate the association between high BMI with the laboratorial and clinical outcomes of patients undergoing ART. Methods: Retrospective cohort study, with data collection from electronic medical records of patients from a reproductive medicine center in Porto Alegre, Brazil, between 2013-2020. Patients' cycles were divided into three groups according to BMI (kg/m²): Group 1 < 25; Group 2 25-29.9 and Group 3 ≥30. Quantitative variables were compared in median (IIQ) and categorical as percentage. Generalized estimating equations (GEE) were applied to consider patients and follicle-aspiration cycles, and also ANOVA and Chi-square tests, multiple logistic regression and post-hoc curve were applied according to the variables analyzed. It was considered statistically significant p <0.05. The sample size was enough for a 12% power. Results: A significant linear tendency to a higher proportion of cancelled IVF cycles as higher as was the BMI was observed (6.9% vs 7.8% vs 10.4%, p= 0.002). We also found a higher gonadotropin's total dose in groups 2 and 3 (1685±595 vs. 1779±610 vs. 1805±563 p=0.001). A greater number of mature oocytes was observed in Group 1 and 2 (6 [6.4-7] vs 6 [5.6-6.6] vs 4 [4.6-6.7], p= 0.0111), but no difference between oocyte mature rate. Lower but not statistically significant implantation (%) (28.4 vs 27.5 vs 23.2, p = 0.187), clinical pregnancy (%) (40.1 vs 39.7 vs 32.5, p= 0.262) and live birth rates (%) (33.5 vs 32.3 vs 29.9, p = 0.668) was found in groups 2 and 3. We also observed that the higher the BMI, the worse was the cumulative clinical pregnancy rate, with significant linear tendency (p=0.042). Perinatal outcomes were similar between groups (maternal and newborn conditions). Conclusion: Overweight and obesity were associated with higher cancelation rates, higher gonadotropine doses and lower, but not statistically different chances of implantation, clinical pregnancy and live birth rates.